Struktur, Kategori, dan Fungsi Sosial Pertanyaan Tradisional (Riddles) Masyarakat Korong Taluak Nibuang Tanjung Medan Nagari Sandi Ulakan Kecamatan Ulakan Tapakis Kabupaten Padang Pariaman - Fanny Febyola; Hasanuddin WS (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
The purpose of this study is to describe (1) the traditional question structure (riddles) of the Korong Taluak Nibuang Tanjung Medan Nagari Sandi Ulakan community, Ulakan Tapakis District, Padang Pariaman Regency, (2) Traditional question categories (riddles) for the Korong Taluak Nibuang community, Tanjung Medan Nagari Sandi Ulakan, Ulakan Tapakis District, Padang Regency. Pariaman, and (3) Social function of traditional questions (riddles) for the people of Korong Taluak, Nibuang Tanjungn, Medan, Nagari, Sandi Ulakan, Ulakan Tapakis District, Padang Pariaman Regency. This type of research uses a qualitative descriptive method. The traditional questions (riddles) of the Korong Taluak Nibuang community, Tanjung Medan, Nagari Sandi Ulakan, Ulakan Tapakis District, Padang Pariaman Regency, will be used as research data. The process of collecting information from informants, which took place in two stages: recording and collecting data about the storyteller's background. There are four stages in the data analysis process: (1) data copying, (2) data classification, (3) discussion and interpretation of findings (4) reporting research findings that reveal the following: (1) the traditional question structure (riddles) of the Korong community Taluak Nibuang Tanjung Medan Nagari Sandi Ulakan Ulakan Tapakis District, Padang Pariaman Regency consists of: (a) conflicting riddles, and (b) non-conflicting traditional questions (riddles). (2) the categories of traditional questions (riddles) for the Korong Taluak Nibuang community, Tanjung Medan Nagari Sandi Ulakan, Ulakan Tapakis District, Padang Pariaman Regency, include (a) similarities to humans, (b) similarities to animals, (c) similarities to inanimate objects, (d) equations with plants, and (e) similarities with color. (3) the social function of traditional questions (riddles) in Korong Taluak Nibuang Tanjung Medan Nagari Sandi Ulakan, Ulakan Tapakis District, Padang Pariaman Regency, consists of: (a) intelligence testing, and (b) entertainment.